PLAGIARISME DALAM KATA-KATA MAHASISWA: ANALISIS TEKS DENGAN PENDEKATAN FUNGSIONAL - Siti Wachidah (Masyarakat Linguistik Indonesia, 2013)
The study analyses students’ statements about plagiarism. The aim was to obtain an analytical understanding about their concepts of plagiarism in, particularly, academic writing. Respondents were 47 students of seven different universities in Java, Sumatra, Bali, and Sulawesi who were currently woking on their skripsi. The data consisted of statements they wrote to answer four open questions, including definitions of plagiarism, plagiarism practices they knew, their views of advantages and diadvantages of plagiarism, and reasons of plagiarism.The statements were analysed for their transitivity aspects by using the systemic functional linguistic procedure to identify the processes, participants, and circumstances. In this way, the particular acts of plagiarism, the objects of plagiarism, and the circumstances of plagiarism can be vividly specified. The study found that the students had good understanding concerning the acts and objects of plagiarism, but incomplete or incorrect understanding concerning the circumstances of plagiarism. It is a good sign thoughthat plagiarism was generally associated with words with unfavorable meanings, the occurrence of which being driven by circumstances beyond the students’ control.